Efektivitas Akar Vetiver Terhadap Peningkatan Kohesi Tanah Lereng Sebagai Tinjauan Untuk Perkuatan Lereng - Nurul Badriyah; Sri Wulandari (Institut Teknologi Bandung, 2020)
AbstractStrengthening slope by bio-engineering/ vegetative method is one of the effort to handle landslides on the slopes by utilizing plants. The purpose of this study was to evaluate the effectiveness of vetiver roots in increasing slope soil cohesion as a review of slope reinforcement. The study was conducted by modeling slope in a model with dimensions of 150 cm Ã— 50 cm Ã— 70 cm with a slope of 70° and 80° as well as soil property testing before and after retrofitting in the laboratory, both physical and mechanical. The mechanical test carried out is testing the shear strength directly on the sample before and after planting Vetiver at a depth of 0